On subshifts and semigroups - Krieger, Wolfgang (Bulletin of the London Mathematical Society, 2016)
Semigroups (with zero) and inverse semigroups (with zero) are constructed from subshifts. The semigroups and inverse semigroups that are obtained by this construction are characterized and classified.